1972
DOI: 10.1002/mrc.1270040410
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance studies of compounds with bridgehead nitrogen atoms—XX: The NMR spectra and stereochemistry of some hexahydropyrido[2, 1‐c] [1, 4] oxazin‐3(4H)‐ones and related compounds

Abstract: A series of substituted hexahydropyrido[2,1-c][l,4]oxazin-3(4H)-ones has been synthesised, and the configurations of these bicyclic lactones assigned utilising chemical and spectral data. All the compounds adopt frans-fused conformations and the conformation of the lactone ring is discussed with reference to the magnitude of the geminal coupling constant of the N-CH,-C(0)-0 protons, and the vicinal couplings between the angular proton and the methylene protons adjacent to the ring oxygen atom. The lactone ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recrystallization from ethanol gave an analytical sample, mp 168-183 °C. The NMR spectrum showed that the sample tra/is-TV,iV-Diethyl-1,3,4,6,7,1 lb-hexahydro-9,10-methylenedioxy [ 1,4]oxazino [3,4-a ]isoquinoline-3-carboxamide (31). The above mixture of cis and trans nitriles was refluxed with 0.5 N ethanolic potassium hydroxide (40 mL) and water (8 mL) for 4 h. The solvents were removed in vacuo (80 °C) to give a gummy residue which was dissolved in 2.5 N aqueous hydrochloric acid (15 mL) and allowed to crystallize on standing overnight.…”
Section: -Hydroxy-3-(34-methylenedioxyphenethylamino)-mentioning
confidence: 99%
See 3 more Smart Citations
“…Recrystallization from ethanol gave an analytical sample, mp 168-183 °C. The NMR spectrum showed that the sample tra/is-TV,iV-Diethyl-1,3,4,6,7,1 lb-hexahydro-9,10-methylenedioxy [ 1,4]oxazino [3,4-a ]isoquinoline-3-carboxamide (31). The above mixture of cis and trans nitriles was refluxed with 0.5 N ethanolic potassium hydroxide (40 mL) and water (8 mL) for 4 h. The solvents were removed in vacuo (80 °C) to give a gummy residue which was dissolved in 2.5 N aqueous hydrochloric acid (15 mL) and allowed to crystallize on standing overnight.…”
Section: -Hydroxy-3-(34-methylenedioxyphenethylamino)-mentioning
confidence: 99%
“…Anal. (C16H20N2O4) C, , N. trans-l, 3,4,6,7, llb-Hexahydro-9,10,1 l-trimethoxy [ 1,4]oxazino [3,4-a]isoquinoline-3-carboxamide (34). A mixture of the above nitrile (3.7 g), 0.51 N potassium fert-butoxide in teri-butyl alcohol (25 mL), and teri-butyl alcohol (370 mL) was refluxed for 2 h and evaporated.…”
Section: -Hydroxy-3-(34-methylenedioxyphenethylamino)-mentioning
confidence: 99%
See 2 more Smart Citations